2020
DOI: 10.3390/en13102468
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Fuels from Forestry Biomass Residue: Torrefaction Process of Horse Chestnuts, Oak Acorns, and Spruce Cones

Abstract: The global energy system needs new, environmentally friendly, alternative fuels. Biomass is a good source of energy with global potential. Forestry biomass (especially wood, bark, or trees fruit) can be used in the energy process. However, the direct use of raw biomass in the combustion process (heating or electricity generation) is not recommended due to its unstable and low energetic properties. Raw biomass is characterized by high moisture content, low heating value, and hydrophilic propensities. The initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 62 publications
0
23
0
Order By: Relevance
“…The impact of thermal processing on the physicochemical properties of many popular types of biomass is known. The studies about biomass torrefaction and pyrolysis [10][11][12][13][14][15] showed that the higher temperature of the biomass processing improves its thermal properties. The biochar is characterized by higher heating value, lower moisture content, lower volatile matter content, and improved hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of thermal processing on the physicochemical properties of many popular types of biomass is known. The studies about biomass torrefaction and pyrolysis [10][11][12][13][14][15] showed that the higher temperature of the biomass processing improves its thermal properties. The biochar is characterized by higher heating value, lower moisture content, lower volatile matter content, and improved hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…The biochar is characterized by higher heating value, lower moisture content, lower volatile matter content, and improved hydrophobicity. The torrefied biomass is initially sterile and much more resistant to decay, and therefore it can be stored for a longer time [11]. As it is known, the first stage in thermal processes is dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…It takes place at 200-320 • C in the absence of oxygen. Solids are the main process products [22]. The pyrolysis also takes place in the absence of oxygen but at temperatures over 320 • C. As a result, depending on pyrolysis conditions main products are liquid, gas, or solid; nevertheless, amounts of solids obtained from pyrolysis always are lower than from torrefaction.…”
Section: Peat Thermal-upgrading Methodsmentioning
confidence: 99%
“…Activated carbons derived from various types of chestnuts were also investigated for several other applications [ 9 , 10 , 39 , 40 , 41 , 42 , 43 ]. For instance, chestnut shells served as a raw material for the preparation of biochar with high calorific value as a potential fuel [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chestnut cupulae was used by Kar et al for the preparation of bio-oil, serving as fuel or chemical feedstock [ 40 ]. Dyjakon et al studied forest biomass containing horse chestnuts as an alternative fuel [ 41 ]. Biochar from chestnut shells supported with carbon nanotubes was examined as an adsorbent for heavy metals contaminants by Yang et al [ 9 ].…”
Section: Introductionmentioning
confidence: 99%